Hop Tropicalization: Chemical Compositions of Varieties Grown under Organic and Conventional Systems in Subtropical Conditions - Fortuna, Gabriel Cássia [UNESP]; Neves, Caio Scardini [UNESP]; Campos, Olivia Pak [UNESP]; Gomes, Jordany Aparecida Oliveira [UNESP]; Silva, Júlio César Rodrigues Lopes [UNESP]; Souza, Amauri Alves [UNESP]; Funari, Cristiano Soleo de [UNESP]; Marques, Márcia Ortiz Mayo; Bonfim, Filipe Pereira Giardini [UNESP] (MDPI, 2023)
The interest in the production of hops in Brazil, motivated by the third position in the world ranking of beer producers and the growth of the craft brewery business, justifies the intensification of studies into its adaptation to local growing conditions. Due to the high internal demand, the aim of this study was to evaluate the phytochemical profiles of hop varieties grown in subtropical conditions under different cropping systems. Studies that promote the expansion of cultivation areas in distinct climate conditions and ensure quality are very important. A randomized block design was adopted with a 2 × 5 subdivided plot. The main factor was the cropping system (organic and conventional), and the secondary factor was the hop variety (Columbus, Chinook, Nugget, Cascade and Hallertau Mittelfrüeh), with four blocks and four plants per plot. The quality parameters monitored in this work were the contents of alpha and beta acids, and xanthohumol in the inflorescences of hops, as well as the relative composition of their essential oils. The variations in the chemical profiles of essential oils showed differences between some varieties, and the different compositions and levels resulting from the two cropping systems show that management and cultural practices can influence the aromatic characteristics of hops; in total, 23 compounds were found. The terpene fraction represented 79.67% of the oil in Hallertau and 93.63% in Cascade, with myrcene being the main compound. The levels of bitter acids and xanthohumol did not differ statistically as a function of the treatments. This study contributes the first records of the chemical profiles of hops grown in subtropical conditions in Brazil, in general, the Nugget variety had the highest qualitative potential
Keywords: alpha and beta acids; Brazilian hops; essential oil; management; phytochemical profile; xanthohumol